2009
DOI: 10.1074/jbc.m809456200
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Pooled Peptides with Intact Protein for Accessing Cross-presentation Pathways for Protective CD8+ and CD4+ T Cells

Abstract: To better understand the mechanisms of intracellular trafficking and presentation of exogenous peptides by antigen-presenting cells (APC), we compared the handling of overlapping 24-mer peptides from HIV Nef either mixed or covalently linked in tandem in one protein. Once internalized, peptides trafficked not only to endosomes but also to cytosol, and activated CD8 ؉ and CD4؉ T cells. In contrast, whole protein was found to traffic only to the endosomal compartments, and primarily activated CD4 ؉ T cells. Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 34 publications
6
65
0
Order By: Relevance
“…Our results, however, do not rule out the importance of CD4 T cell-restricted epitopes, and the detection of cytokines other than IFNg might be useful to confirm or refute these findings. Additionally, using the entire 21OH protein instead of peptide pools in the ELISPOT assay would probably facilitate the identification of autoreactive CD4 T cells [34]. However, purification of the correctly-folded entire 21OH was recently reported as quite challenging [35], which may explain the lack of prior identification of 21OH-specific CD4 T cells.…”
Section: Tetramer Analysis Confirms the Presence Of Hla-b8-restrictedmentioning
confidence: 99%
“…Our results, however, do not rule out the importance of CD4 T cell-restricted epitopes, and the detection of cytokines other than IFNg might be useful to confirm or refute these findings. Additionally, using the entire 21OH protein instead of peptide pools in the ELISPOT assay would probably facilitate the identification of autoreactive CD4 T cells [34]. However, purification of the correctly-folded entire 21OH was recently reported as quite challenging [35], which may explain the lack of prior identification of 21OH-specific CD4 T cells.…”
Section: Tetramer Analysis Confirms the Presence Of Hla-b8-restrictedmentioning
confidence: 99%
“…SLPs are designed as approximately 30-mer peptides overlapping by 10 to 15 amino acids, whereby the length strongly favours peptide processing by 'professional' antigenpresenting cells to direct binding to major histocompatibility complex (MHC) class I on the cell surface; this provides a parallel stimulation of both CD4 þ helper and CD8 þ cytotoxic T cells [14,15]. Nevertheless, SLP immunogenicity requires optimal peptide adjuvantation [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The antigen presentation resulting from SLP vaccination reflects physiological pathways associated with much lower, and therefore more appropriate, MHC-ligand presentation than the uncontrollable and usually too-high peptide loading resulting from short peptide vaccination (Figure 2). We and others have shown that only DCs are capable of efficiently processing such SLPs for presentation in both MHC class I and class II molecules (140,141) and that such processing is much more efficient than that of intact proteins (141,142). Moreover, SLPs typically harbor both CD4 + and CD8 + T cell epitopes, ensuring that vaccination with SLPs induces a balanced CD4/CD8 response.…”
Section: Guidelines For the Development Of Successful Therapeutic Canmentioning
confidence: 99%